Conceptual Study On Samprapti (Pathogenies) Of Śvitra w.s.r To Vitiligo - Saini, Shree Ram; Sevatkar, B K (International Research Journal of Ayurveda & Yoga, 2021)
Skin is the first organ of the body interacting with the environmental agents like physical, chemical & biological agents. Variations in the environmental stimuli & natural ability of body to deal with these factors result in spontaneous remissions & relapses. Interaction with these factors results in specific reaction pattern producing characteristic skin lesions in different parts of the body. Skin is a mirror that reflects internal & external pathology & thus helps in diagnosis of diseases. Skin ailments affects all ages from the neonates to the elderly & cause harm in a number of ways, such as discomfort, disfigurement, disability, etc. Svitra (Vitiligo) can be correlated with Vitiligo in contemporary medicine. Vitiligo is an autoimmune disease against melanocyte characterized by hypopigmented patches. In this review article describe the Ayurvedic Samprapti (Pathogenesis) in detail according to Ayurveda.